Epipalaeolithic and Pre-Pottery Neolithic burials from the north Lebanese highlands in their regional context. (2nd January 2018) - Garrard, Andrew; Edwards, Yvonne; Stock, Jay; Yazbeck, Corine
Abstract : Archaeological human remains and their funerary contexts provide valuable insights into social and ideological lives as well as the origins, health and activities of past communities. In the southern Levant extensive cemeteries from the Late Epipalaeolithic (Natufian) and Pre-Pottery Neolithic (PPN) have been recognized, although burials from earlier periods are sparse. Elsewhere in the Levant the record from the whole Epipalaeolithic is poor. Excavations at two adjacent caves at Moghr el-Ahwal in the Qadisha Valley of northern Lebanon have provided a window into human lives and mortuary practices from an otherwise poorly known region. This includes material from contexts with radiocarbon dates ranging from the late Kebaran, Geometric Kebaran and Natufian ( c. 19–13.8 ka cal BP), as well as directly dated skeletal material from the mid to late Pre-Pottery Neolithic B ( c. 9.9–9.5 ka cal BP). Although this forested mountain area may have been isolated from other regions in the Levant, the burial practices show links to the wider area.